Synthesis of novel N-substituted 3-(aminosulfonyl)-2h-l-benzopyran-2-one derivatives and their biological activity - Kovalenko, S.S.; Silin, O.V.; Kovalenko, S.M.; Chernykh, V.P.; Maes, L.; Townson, S.; Yousif, F.; Fakorede, F.; Bernadette, R.; Nwaka, S. (Журнал органічної та фармацевтичної хімії, 2009)
New N-substituted 3-(aminosulfonyl)-2H-1 -benzopyran-2-one derivatives were synthesized by the reaction of salicylic aldehydes with N-substituted ethyl 2-(aminosulfonyl)acetates in the Knoevenagel condensation conditions. The structure of obtained compounds was determined through a complete IR- and ¹H NMR analysis. The biological activity of some derivatives against protozoan and helminth parasites was studied. Some compounds were active against Onchocerca lienalis. Нові N-заміщені похідні 3-(аміносульфоніл)-2Н-1 -бензопіран-2-онів були синтезовані за реакцією саліцилових альдегідів з N-заміщеними етил 2-(аміносульфоніл)ацетатами в умовах конденсації за Кньовенагелем. Структуру отриманих сполук було визначено методами ІЧ- та ПМР-спектроскопії. Вивчено біологічну активність отриманих сполук проти протозойних та гельмінтних паразитів. Деякі сполуки виявили високу активність проти Onchocerca lienalis. Новые N-замещенные производные 3-(аминосульфонил)-2Н-1-бензопиран-2-онов были синтезованы реакцией салициловых альдегидов с N-замещенными этил 2-(аминосульфо-нил)ацетатами в условиях конденсации Кневенагеля. Структура полученных соединений была подтверждена методами ИК- и ПМР-спектроскопии. Изучена биологическая активность полученных соединений против протозойных и гельминтных паразитов. Некоторые соединения проявили высокую активность по отношению к Onchocerca lienalis.